South Asia-specific adaptation of Mediterranean diet principles: a mixed-methods review for practical and sustainable dietary habits - Spadaccini, Daniele; Chandran, Arun; Gonçalves Correia, Filipa Patricia; Janji, Helia; Ciamparini, Carola; Tini, Sabrina; Caputo, Marina; Marzullo, Paolo; Aimaretti, Gianluca; Prodam, Flavia (Frontiers in Nutrition, 2025)
South Asia, home to nearly 2 billion people, faces a dual burden of persistent malnutrition and rapidly rising rates of obesity, type 2 diabetes, and cardiovascular diseases. Dietary patterns are dominated by refined cereals, low intake of fruits, vegetables, and whole grains, limited protein quality, and imbalanced fat composition, compounded by cultural practices and the growing penetration of ultra-processed foods. This mixed-method review systematically synthesized dietary intake data and contextual barriers to evaluate the transferability of Mediterranean Diet (MD) principles to South Asia. Unlike broader continental frameworks, our approach integrates local foods, cultural traditions, and environmental realities to design two region-specific dietary pyramids for vegetarian and non-vegetarian populations. The adapted model emphasizes higher consumption of whole grains, legumes, fruits, and vegetables, the inclusion of affordable high-quality protein sources, and a balanced use of locally available fats, while placing sweets and ultra-processed foods at the top of the pyramid with clear limits. Beyond nutrient adequacy, our analysis highlights structural barriers, economic affordability, entrenched food traditions, limited nutritional awareness, environmental pressures, and food safety challenges that must be addressed to ensure feasibility. Policy action, nutrition education, women’s empowerment, climate-smart agriculture, and fortification strategies emerge as key enablers for a sustainable dietary transition in the region.Systematic review registrationhttps://osf.io/d7j4m/